Delivering Flagship Projects in an Era of Regulatory Capitalism: State‐led Privatization and the London Olympics 2012. (27th May 2013) - Raco, Mike
Abstract Much of the urban studies literature on the London Olympics has focused on its social legacies and the top‐down nature of policy agendas. This article explores one element that has been less well covered — the contractual dynamics and delivery networks that have shaped infrastructure provision. Drawing on interviews and freedom of information requests, this article explores the mechanisms involved in the project's delivery and their implications for broader understandings of urban politics and policymaking. It assesses contemporary writings on regulatory capitalism, public–private networks and new contractual spaces to frame the empirical discussion. This article argues that the London Olympic model has been characterized by the prioritization of delivery over representative democracy. Democratic imperatives, such as those around sustainability and employment rights, have been institutionally re‐placed and converted into contractual requirements on firms. This form of state‐led privatization of the development process represents a new, and for some, potentially more effective mode of governance than those offered by traditional systems of regulation and management.